Adverse events following 9-valent human papillomavirus vaccine (GARDASIL® 9) reported to the Vaccine Adverse Event Reporting System (VAERS), 2015–2024 - Qiong Liu; Guojun Liang; Yang Song (Human Vaccines & Immunotherapeutics, 2025)
GARDASIL 9, a 9-valent HPV vaccine approved in 2014, is widely administered for the prevention of HPV-related malignancies. Although clinical trials demonstrated a favorable safety profile, rare or delayed-onset adverse events may not be captured pre-licensure. Post-marketing surveillance using VAERS offers a complementary approach for signal detection and safety monitoring. We conducted a retrospective pharmacovigilance analysis of VAERS reports following GARDASIL 9 administration from January 1, 2015 to December 31, 2024. Adverse events were encoded using MedDRA v26.0 and categorized by System Organ Class. Disproportionality analyses using four independent algorithms (ROR, PRR, IC, EBGM) were applied to identify positive safety signals. Subgroup assessments included serious reports, death reports, and reports in pregnant individuals. Among reported events, most were non-serious and consistent with known reactogenicity patterns, including syncope, headache, and injection site reactions. However, signals were also detected for certain events not listed in product labeling, including postural orthostatic tachycardia syndrome, eye movement disorder, autoimmune thyroiditis, and posture abnormality. In 57 death reports, neurological terms showed signal elevation but lacked consistent etiologic patterns. No positive signals were detected in the 18 pregnancy-associated reports. This VAERS-based analysis supports the established safety of GARDASIL 9 while highlighting rare signals that warrant further investigation. Given the limitations of passive surveillance, integration with active monitoring systems is essential to refine safety profiles and support ongoing public health vaccination efforts.